Active media technology 7th International Conference, AMT 2011, Lanzhou, China, September 7-9, 2011. Proceedings - Zhong, Ning 1956-; Callaghan, Vic; Ghorbani, Ali A.; Hu, Bin; SpringerLink (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 7th International Conference on Active Media Technology, AMT 2011, held in Lanzhou, China, in September 2011. The 30 revised full papers and 6 keynote talks were carefully reviewed and selected for inclusion in the book. They are grouped in topcial sections on data mining and pattern analysis in active media; active human-Web interaction and social media; active Web intelligence applications; active multi-agent and network systems; as well as technology intelligence.
Keynote talks: People's opinion, People's nexus, People's security and computational intelligence: the evolution continues / Ali Ghorbani --Towards conversational artifacts / Toyoaki Nishida --The Global-First Topological Definition of Perceptual Objects, and Its Neural Correlation in Anterior Temporal Lobe / Lin Chen, Ke Zhou, Wenli Qian, and Qianli Meng --Combinatorial Fusion Analysis in Brain Informatics: Gender Variation in Facial Attractiveness Judgment / D. Frank Hsu, Takehito Ito, Christina Schweikert, Tetsuya Matsuda, and Shinsuke Shimojo --Study of System Intuition by Noetic Science Founded by QIAN Xuesen / Zhongtuo Wang --Study of problem solving following Herbert Simon / Yulin Qin and Ning Zhong --Data Mining and Pattern Analysis in Active Media: A Heuristic Classifier Ensemble for Huge Datasets / Hamid Parvin, Behrouz Minaei, and Hosein Alizadeh --Ontology Extraction and Integration from Semi-structured Data / Shaobo Wang, Yi Zeng, and Ning Zhong --Effectiveness of Video Ontology in Query by Example Approach / Kimiaki Shirahama and Kuniaki Uehara --A Survey of Energy Conservation, Routing and Coverage in Wireless Sensor Networks / Wang Bin, Li Wenxin, and Li Liu --A Multi-type Indexing CBVR System Constructed with MPEG-7 Visual features / Yin-Fu Huang and He-Wen Chen --A Novel Data Collection Scheme Based on Active Degree for OMSN / Jianwei Niu, Bin Dai, and Jinkai Guo --Research of Robust Facial Expression Recognition under Facial Occlusion Condition / Bin Jiang and Ke-bin Jia --Active Human-Web Interaction and Social Media: Visualizing Secure Hash Algorithm (SHA-1) on the Web / Dalia B. Nasr, Hatem M. Bahig, and Sameh S. Daoud --Emotion and Rationality in Web Information: An Eye-Tracking Study / Linchan Qin, Ning Zhong, Shengfu Lu, Mi Li, and Yangyang Song --Constructing the Internet Behavior Ontology: Projection from Psychological Phenomena with Qualitative and Quantitative Methods / Qi Zhang, Zhuo-Hong Zhu, Ting-Shao Zhu, Jiu-Ling Xin, Shu-Juan Wang, Wei-Chen Zhang, Ang Li, Yi-Lin Li, Shan Tang, and Yu-Xi Pei --Why Do People Share News in Social Media? / Chei Sian Lee, Long Ma, and Dion Hoe-Lian Goh --Active Web Intelligence Applications: Hot Topic Detection in Professional Blogs / Erzhong Zhou, Ning Zhong, and Yuefeng Li --A Weighted Multi-factor Algorithm for Microblog Search / Lulin Zhao, Yi Zeng, and Ning Zhong --A Combination Ranking Model for Research Paper Social Bookmarking Systems / Pijitra Jomsri, Siripun Sanguansintukul, and Worasit Choochaiwattana --An Upgrading Feature-Based Opinion Mining Model on Vietnamese Product Reviews / Quang-Thuy Ha, Tien-Thanh Vu, Huyen-Trang Pham, and Cong-To Luu --Predicting Mental Health Status Based on Web Usage Behavior / Tingshao Zhu, Ang Li, Yue Ning, and Zengda Guan --User Interests Modeling Based on Multi-source Personal Information Fusion and Semantic Reasoning / Yunfei Ma, Yi Zeng, Xu Ren, and Ning Zhong --Tags Weighting Based on User Profile / Saida Kichou, Hakima Mellah, Youssef Amghar, and Fouad Dahak --A Context-Aware Recommender System for M-Commerce Applications / Jiazao Lin, Xining Li, Yi Yang, Li Liu, Wenqiang Guo, Xin Li, and Lian Li --Towards Coequal Authorization for Dynamic Collaboration / Yuqing Sun and Chen Chen --Active Multi-Agent and Network Systems: Programming Large-Scale Multi-Agent Systems Based on Organization Metaphor / Cuiyun Hu, Xinjun Mao, Yuekun Sun, and Huiping Zhou --A Framework for Context-Aware Digital Signage / Ichiro Satoh --EMTAN: A Web-Based Multi-Agent System Architecture for Input Automation / Ming-Jui Huang, Cheng-Tao Chuang, Kai-Hsiang Yang, and Cheng-Yuan Liou --Estimating the Density of Brown Plant Hoppers from a Light-Traps Network Based on Unit Disk Graph / Viet Xuan Truong, Hiep Xuan Huynh, Minh Ngoc Le, and Alexis Drogoul --Modelling the Behaviour of Crowds in Panicked Conditions / Jake Wendt, Guangzhi Qu, and Jianwei Niu --How to Play Well in Non-zero Sum Games: Some Lessons from Generalized Traveler's Dilemma / Predrag T. Tošić and Philip Dasler --Key Distribution Protocol for Secure Multicast with Reduced Communication Delay / P. Vijayakumar, S. Bose, A. Kannan, and P.H. Himesh --Special Session on Technology Intelligence: Smart Searching System for Virtual Science Brain / Hong-Woo Chun, Chang-Hoo Jeong, Sa-Kwang Song, Yun-Soo Choi, Do-Heon Jeong, Sung-Pil Choi, and Won-Kyung Sung --Using Semantic Web Technologies for Technology Intelligence Services / Seungwoo Lee, Mikyoung Lee, Hanmin Jung, Pyung Kim, Dongmin Seo, Tae Hong Kim, Jinhee Lee, and Won-Kyung Sung --Procedural Knowledge Extraction on MEDLINE Abstracts / Sa-kwang Song, Heung-seon Oh, Sung Hyon Myaeng, Sung-pil Choi, Hong-woo Chun, Yun-Soo Choi, and Chang-hoo Jeong.
Electronic reproduction.
Keywords: Human-computer interaction -- Congresses; User interfaces (Computer systems) -- Congresses; Computer graphics -- Congresses; Multimedia systems -- Congresses; Artificial intelligence -- Congresses; Electronic books